Engagement in online pain self-management improves pain in adults on medication-assisted behavioral treatment for opioid use disorders. (November 2018) - Wilson, Marian; Finlay, Myles; Orr, Michael; Barbosa-Leiker, Celestina; Sherazi, Naghmana; Roberts, Mary Lee A.; Layton, Matthew; Roll, John M.
Abstract: Introduction: Persistent pain has been recognized as an important motivator that can lead individuals to misuse opioids. New approaches are needed to test pain treatments that can improve outcomes for people with persistent pain in medication-assisted behavioral treatment for opioid use disorder. This study piloted an online pain self-management program to explore acceptability and treatment effects. Methods: A sample of 60 adults diagnosed with chronic non-cancer pain and receiving medication-assisted behavioral treatment at one of two clinics were randomized into either treatment group with access to an online pain management program or waitlist attention control. Participants received online surveys via email at baseline and post-treatment at week 8. Results: The majority of participants (n = 44; 73%) reported that their first use of opioids was in response to a painful event. Those who engaged in the online program had significantly lower pain interference, pain severity, opioid misuse measures, and depressive symptoms after eight weeks while pain self-efficacy was increased. Conclusion: Our results suggest the online pain self-management program content may be helpful for managing physical and emotional symptoms experienced by individuals with co-occurring pain and opioid use disorders. To improve online engagement, more support is necessary to assist with technology access and completion of online activities. Highlights: Online pain programs can reduce symptoms for people with pain and opioid use disorders. Pain self-efficacy is inversely related to pain, depression and opioid misuse. Strategies to improve online program engagement are needed.